Regulation of lung immunity and host defense by the intestinal microbiota - Samuelson, Derrick R.; Welsh, David A.; Shellito, Judd E. (Frontiers in Microbiology, 2015)
Every year in the United States approximately 200,000 people die from pulmonary infections, such as influenza and pneumonia, or from lung disease that is exacerbated by pulmonary infection. In addition, respiratory diseases such as, asthma, affect 300 million people worldwide. Therefore, understanding the mechanistic basis for host defense against infection and regulation of immune processes involved in asthma are crucial for the development of novel therapeutic strategies. The identification, characterization, and manipulation of immune regulatory networks in the lung represents one of the biggest challenges in treatment of lung associated disease. Recent evidence suggests that the gastrointestinal (GI) microbiota plays a key role in immune adaptation and initiation in the GI tract as well as at other distal mucosal sites, such as the lung. This review explores the current research describing the role of the GI microbiota in the regulation of pulmonary immune responses. Specific focus is given to understanding how intestinal “dysbiosis” affects lung health.